Theoretical model of yield strength for eutectic colony microstructure materials. (1st July 2023) - Wang, Liyang; Ye, Bing; Huang, Wei; Ding, Wenjiang
Abstract: Eutectic alloys have a wide range of applications and have been studied in numerous experiments and simulations. However, there is no model available to describe the contribution from the morphology on strength of the eutectic structure. The model for eutectic strengthening σsp = ksp f λ −1/2 is derived from the Brown model and Taylor-Orowan's equation. The equation reveals the relationship between yield strength and eutectic features including slip parameter, effective shear modulus, second phase volume fraction and eutectic spacing. The equation predictions agree well with the experimental measurements for both Al-Ce and Fe28 Ni18 Mn33 Al21 alloys. The model may effectively predict the yield strength of eutectic alloys and provide insights for eutectic strengthening. Graphical abstract: Image, graphical abstract